SP9.1.4 Management of Small Bowel Obstruction: A Comparison to NASBO. (28th October 2021) - Ahmed, Babur; Thompson, Anna; Colgan, Aoife; Brindle, Rachel
Abstract: Aim: Prompt diagnosis and proactive decisions in management of small bowel obstruction (SBO) can reduce the associated morbidity, in-hospital stay and mortality. Following recommendations of National Audit of Small Bowel Obstruction (NASBO) and Bologna (2017), the "agreed pathway" of The Association of Surgeons of Great Britain and Ireland (ASGBI, 2018) sets clear guidelines to aid timely management of SBO. We aimed to audit our practice to these guidelines and compared outcomes to NASBO. Methods: Data was collected retrospectively on patients admitted with SBO from July 2019 - December 2019 and presented as percentage, median or interquartile range (IQR). Results: Median age of 76 included patients was 62.0 years, 53.9% were female. Aetiologies were; adhesions (59.2%), hernia (27.6%), malignancy (10.5%) and others (2.6%). Admission CTs were performed in 92.1% vs. 80.0% (NASBO), with a median time of 3.3 hours vs. 2.2 days (NASBO). Median time to surgery in those managed operatively ( n  = 35) was 10 hours vs. 1 day (NASBO), while in 72.0% vs. 21.0% (NASBO) of non-settling SBO, water soluble contrast study (WSCS) was performed in a median (IQR) time of 39.0 (20.0-45.4) hours. Adhesional SBO resolved in 85.7% of cases suitable for non-operative approach. Objective nutritional assessment was performed in 94.7% vs. 90.0% (NASBO). In-hospital stay, 30-day morbidity and mortality compared to NASBO were 5.0 vs. 10.7 days, 31.6% vs. 23.0% and 5.3% vs. 8.0% respectively. Conclusion: ASGBI guidelines provide multi-faceted proactive approach in managing SBO; including early cross-sectional imaging, prompt WSCS use and timely nutritional interventions, promoting improved outcomes.